Parking Lot Cities: Examining the Impacts of Parking Policy Reform on Autocentric Development Patterns In Buffalo, New York, and Hartford, Connecticut. - Trollinger, Brenna. (Tufts University. Tisch Library., 2023)
Thesis (M.A.)--Tufts University, 2023.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Christine Cousineau.; Committee: Mark Chase.; Keywords: Urban planning, and Transportation.